ТЕОРЕТИЧНИЙ АНАЛІЗ РУХУ НАСІННЯ У МІЖДЕКОВОМУ ПРОСТОРІ ВІБРОФРИКЦІЙНОГО СЕПАРАТОРА (Science journal «Technical service of agriculture, forestry and transport systems», 2026)
Theoretical studies of the movement of the components of seed mixtures in the inter-deck space are presented, taking into account the influence of the air flow, which is formed due to the oscillatory movement of the working body, the most appropriate intervals for varying the structural and operating parameters of the vibro-friction separator are revealed. It was established that an increase in the frequency and amplitude of oscillations of the working body of the separator leads to an increase in the average speed of the seed, the maximum speed of particle movement is achieved in the interval of changing the parameters: A = 1.0…1.7 mm; ɷ = 200…260 s-1. A further increase in these parameters leads to a decrease in the rate of vibrational movement. When the speed of movement of the working body (Aɷ) is more than 27…30 cm/s, the influence of the air environment leads to a decrease in the speed of vibrational movement of the particle. Therefore, to ensure the maximum productivity of the process, the speed of movement of the working body should not exceed the above values. The average speed of movement of particles tends to decrease as the value of the angle α increases, and when a certain value of the angle of inclination is reached, the particle stops, and with a further increase of α, it moves in the opposite direction. A particle with a smaller value of the coefficient of instantaneous friction λ changes the direction of movement at a smaller value of the angle of inclination of the plane, and with a larger value of λ - at a larger value of α, when the process of separating the components of the NS is realized. Changing the direction angle of oscillations ε does not have such a significant effect on the speed of seed movement as the amplitude and frequency of oscillations, an increase in ε to 35 40° ensures an increase in the speed of movement, and a further increase in the angle ε leads to a decrease in the average speed of seed movement along the working body. The highest performance of the vibro-friction separator can be achieved when using ε = 35…40°. It has been proven that when the gap H increases from 3 to 6 mm, the speed of movement decreases, and when the gap is further increased, it increases and remains constant after 12 mm. Less expedient, from the point of view of the speed of movement of components of the NS on the working surface, is a gap between the decks of the vibro-friction separator in the range of 3.5…10 mm.
Keywords: vibro-separation; seed mixture; vibro-friction separator; parameters of the vibro-friction separator; quality of separation; vibro-displacement